Vegetation creates microenvironments that influence soil microbial activity and functional diversity along an elevation gradient. (February 2022) - Hernández-Cáceres, Daniel; Stokes, Alexia; Angeles-Alvarez, Guillermo; Abadie, Josiane; Anthelme, Fabien; Bounous, Manon; Freschet, Grégoire T.; Roumet, Catherine; Weemstra, Monique; Merino-Martín, Luis; Reverchon, Frédérique
Abstract: Soil microbial communities are responsive to abiotic and biotic conditions within the heterogeneous soil environment. In montane plant communities, vegetation can create distinctive microenvironments that have unique microbial responses. Here, we ask how soil microbial activity and functional diversity were influenced by the type and diversity of montane plant species, and the morphological and chemical traits of their associated root systems, that are expected to influence soil properties. Along an elevational gradient (1400-2400 m a.s.l.) in the French Alps, we investigated microbial global catabolic activity (i.e. microbial activity) and catabolic diversity (i.e. functional diversity) in bulk and rhizosphere soil beneath three plant species ( Vaccinium myrtillus, Juniperus communis and Picea abies ) using multiple substrate-induced respiration. We also measured soil physical and chemical properties, plant diversity, climatic factors and morphological and chemical traits of roots in bulk soil (' community ' level traits, where several plant species were pooled together) and of individual plants (' species ' level, where roots of single species were excavated). At lower elevations, global catabolic activity in the rhizosphere was higher than in bulk soil, but converged in the nutrient-poor, colder soils found at higher elevations, although changes in catabolic diversity were negligible. Variations in soil texture, cation exchange capacity, carbon and nitrogen content and pH were associated with the global catabolic activity, but these soil properties had minimal effects on catabolic diversity. Climatic variables were related to microbial activity beneath V. myrtillus only and warmer mean annual temperatures increased activity. Plant root traits at the community level in bulk soil had less effect on global catabolic activity than abiotic factors, with thicker roots, high root lignin content and low cellulose content influencing microbial activity, but not altering catabolic diversity. At the species level, more dense root tissue decreased global catabolic activity, reflecting changes in chemical composition. Overall, our results show that soil physical and chemical properties were the main drivers of microbial activity, but that vegetation created distinctive microenvironments that refined these relationships, mainly through modifications in root chemical traits. Highlights: Soil physical and chemical properties were the main drivers of microbial activity. Microbial activity converged in bulk and rhizosphere soils at higher elevations. Plant species identity refined relationships with microbial activity and abiotic factors.